PENGARUH KUALITAS SUMBER DAYA MANUSIA, MANFAAT TEKNOLOGI INFORMASI, DAN SISTEM PENGENDALIAN INTERN TERHADAP KETERANDALAN PELAPORAN KEUANGAN PADA LPD SE – KECAMATAN PUPUAN - I Putu Daniarsa (UNHI Press, 2021)
This study aims to determine the effect of the quality of human resources, the benefits of information technology and internal control systems on the reliability of financial reporting. The population in this study were LPD employees who were in the Pupuan sub-district. The sample collection technique used purposive sampling in order to obtain a sample size of 60 people. Data were analyzed using multiple linear regression analysis. Based on the results and discussion, it can be concluded that all research variables, namely the quality of human resources, the benefits of information technology, and the internal control system have an influence on the reliability of financial reporting.